Cell therapy for ischaemic stroke - Hess, D. C. (Cell Prolif, 2011)
While acute neuroprotection in acute stroke has proven difficult and ended in many failures, there is increasing interest in restorative therapies that target brain remodelling. Cell therapy (transplantation of cells) shows promise, with a growing body of pre‐clinical evidence demonstrating improved functional outcomes in animal models; however, questions still remain concerning mechanisms of action. Clinical trials are already underway and will increase in the next few years; their appropriate design and execution along with continued pre‐clinical work are necessary for the field to advance and satisfy a large unmet clinical need.